Recurrent pulmonary mucormycosis after lobectomy in a non-smoking patient without predisposing risk factors - Zhang,Lu (2012)
Pulmonary mucormycosis is a very rare clinical condition in patients without underlying risk factors. A limited number of cases have been reported in predominantly elderly patients; history of smoking appears to be a common feature. A case of non-smoking male who developed pulmonary mucormycosis with the longest reported follow-up is presented. In addition, this is also the first reported case with disease recurrence after lobectomy (two years) in an immunocompetent host. Treatment with an additional lobectomy and amphotericin B was successful in this patient.